Waqf and Sustainability Efforts: Islamic Philanthropy Against Global Change - Rahmayati, Rahmayati; Badawi, Afif (Risalah Iqtishadiyah, 2024)
Waqaf, as an instrument of Islamic philanthropy, has great potential to contribute to social and economic welfare. This research aims to explore the role of waqf in supporting sustainability as a form of Islamic philanthropy in the context of global change. The findings of this research examine waqaf's contribution to sustainability efforts in the face of global change and identify key barriers to effective waqaf implementation. The lack of clear and uniform regulatory standards regarding waqaf in different countries, leading to difficulties in management and enforcement and a lack of knowledge and skills in waqaf management among managers and stakeholders. Blockchain technology offers a solution that can improve the efficiency and effectiveness of waqaf management, by creating a more transparent, accountable and secure system. Therefore, international collaboration and the implementation of modern technologies such as blockchain are necessary to maximize waqaf's contribution in facing global change and achieving sustainability goals.